Design considerations for libraries providing a barrier-free library for the disabled - Mendoza, Elmer Amiel F. (2001)
Libraries are the great vaults of knowledge. its purpose is to give the information needs of varied clients. Today, this purpose is being negated, because of some faults in building as well as facility designs. Mobility impaired individuals are being left out, because they cannot access the collections in the libraries. They find it hard to enter and roam around the library premises.